The Relationship between Workload and Psychological Fatigue (Burnout) - Waldani, Dina; Gustina Indriati (RADINKA JAYA UTAMA PUBLISHER, 2023)
Workload is the amount of work that must be carried by a position or organizational unit and is the product of the volume of work and the time norm. Researchers conducted a pre-survey of 10 employees at Bank BTN KC Padang in the Teller and Marketing section, 8 employees who were pre-survey respondents answered